Skills and planning of training needs in hospitality in Bogotá, Colombia - Zurbarán-Arias, Deiwi Jesús (2024)
This study examines training practices in Bogotá’s hotel sector, focusing on developing technical and interpersonal competencies and adapting them to sustainable practices and technologies. Through interviews and proposal analysis, areas for improvement are identified, such as implementing continuous feedback and recognition systems to motivate and retain staff. Key findings highlight the importance of interpersonal skills in optimising the guest experience and training in sustainability and digital tools management. The article proposes establishing an internal training school for continuous, specialised development and suggests partnerships with educational institutions to strengthen training programs, improve service quality, and meet modern customer expectations. These strategies would contribute to greater competitiveness and sustainability in Colombia’s hotel sector.